The Impacts of the “Exponential Era” on Public Management in Emerging Countries - Oszlak, Oscar (Revista del CLAD Reforma y Democracia, 2020)
This paper aims to analyze and forecast the foreseeable impacts on public management that may be caused by the technological developments that characterize this exponential era (ICT, big data, AI, robotics and their applications). The work focuses on emerging countries and their relative weakness to mitigate the negative impacts of these changes and to take advantage of innovation, presenting several ideas and recommendations on how to promote awareness and start a systematic reflection on the subject. The paper examines: 1) the social and economic impacts of technological innovations that characterize the current exponential era; 2) the deepening of disparities between the advanced countries leading these changes and the emergent countries that show little concern about their impact; and 3) the ethical and cultural considerations that must be solved as a result of technological developments.